1998
DOI: 10.1177/002215549804600311
|View full text |Cite
|
Sign up to set email alerts
|

Immunofluorescence Characterization of Key Extracellular Matrix Proteins in Murine Bone Marrow In Situ

Abstract: SUMMARYThe mechanism of hemopoietic stem cell homing to the bone marrow involves molecular interactions that mediate the recognition and interaction of these cells with the marrow microenvironment, including the extracellular matrix. On selective binding, this environment, in combination with soluble cytokines, regulates stem cell proliferation and differentiation. Using immunofluorescence labeling, we analyzed the location of the prominent extracellular matrix proteins fibronectin, collagen Types I, III, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
142
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(152 citation statements)
references
References 29 publications
9
142
0
1
Order By: Relevance
“…The localization of both laminin and type IV collagen in bone marrow sinusoidal basement membrane seen in the present study accords with previously reported immunofluorescence studies of basement membranes demonstrating a close co-localization of these two major components (Nilsson et al, 1998;Reilly et al, 1985). In addition to the lack of HSPG, certain observations in this study remain to be correlated with the observed inability to form typical basement membrane structures.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The localization of both laminin and type IV collagen in bone marrow sinusoidal basement membrane seen in the present study accords with previously reported immunofluorescence studies of basement membranes demonstrating a close co-localization of these two major components (Nilsson et al, 1998;Reilly et al, 1985). In addition to the lack of HSPG, certain observations in this study remain to be correlated with the observed inability to form typical basement membrane structures.…”
Section: Discussionsupporting
confidence: 93%
“…Their biochemical nature could not be established with certainty based on ultrastructural features alone. However, their appearances strongly suggest that they were made up of type IV collagen molecules because (1) the width of single and two-to-three laterally-associated molecules of type IV collagen measure 1.5, 2-2.5, and 3 nm, respectively (Table 1; Inoue et al, 1983;Inoue, 1994;Inoue and Leblond, 1988), and (2) immunohistochemical evidence has shown type IV collagen to be a major component of the sinusoidal basement membrane in bone marrow (Reilly et al, 1985;Nilsson et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it seems inevitable in BM (Fig. 1A) that migrating MKs encounter gradients in both tissue elasticity and collagen density (20). The bone surface is high in collagen-I (collagen hi ) and stiff, with an estimated elasticity E ECM for osteoid of ∌34 kPa (2), whereas the marrow space is collagen lo and very soft, approximated here with E ECM = 0.3 kPa (21).…”
Section: Results and Analysismentioning
confidence: 95%
“…CXCL12 is produced by a number of micro-environmental cells, including CXCL12-abundant reticular (CAR) cells [22], nestin+ cells [23], cells of the osteoid lineage [24], arteriolar pericytes [25], and endothelial cells [26]. Once produced, CXCL12 may be bound to matrix components, including fibronectin [27], collagen IV [28], and heparan sulfate [29] expressed within the niche [30,31] potentially refining the activity of this chemokine. Therefore, CXCL12 has the potential to facilitate the retention of HSC in multiple niches within the bone marrow.…”
Section: Introductionmentioning
confidence: 99%